2022
DOI: 10.3389/fphar.2022.1002363
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits angiotensin II-induced vascular smooth muscle cell proliferation and activation of JAK2/STAT3 pathway: A target based networking pharmacology approach

Abstract: The rapid growth of vascular smooth muscle cells (VSMCs) represents crucial pathological changes during the development of hypertensive vascular remodeling. Although quercetin exhibits significantly therapeutic effects on antihypertension, the systematic role of quercetin and its exact mode of action in relation to the VSMCs growth and its hypertension-related networking pharmacology is not well-documented. Therefore, the effect of quercetin was investigated using networking pharmacology followed by in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Quercetin can play a role in anti-hypertension by suppressing Ang II-stimulated VSMC proliferation (Wang et al, 2022). Quercetin may reduce oxidative stress, and minimize arterial endothelial cell dysfunction (Pereira et al, 2018).…”
Section: Bioactive Components and Targets Of Ur-ap In Hypertension Ma...mentioning
confidence: 99%
“…Quercetin can play a role in anti-hypertension by suppressing Ang II-stimulated VSMC proliferation (Wang et al, 2022). Quercetin may reduce oxidative stress, and minimize arterial endothelial cell dysfunction (Pereira et al, 2018).…”
Section: Bioactive Components and Targets Of Ur-ap In Hypertension Ma...mentioning
confidence: 99%
“…Healthy VSMCs are characterized by quiescent contractile phenotype which are transformed into synthetic proliferative and migrative phenotype during progression of hypertension and cardiovascular diseases (Cao et al, 2022). Flavonoids protect against hypertension development by maintaining contractile function of vascular smooth muscle cells by decreasing their growth (Wang et al, 2022; Wu et al, 2018). Flavonoids inhibit the activity of ACE (Guerrero et al, 2012).…”
Section: Flavonoids: Potential Mechanisms Beyond Vascular Tone Regula...mentioning
confidence: 99%
“…In addition, quercetin has been shown to inhibit angiotensin II-induced vascular smooth muscle cell proliferation and activation of the JAK2/STAT3 pathway [4; 27]. The KEGG pathway assessment showed that quercetin affects various signalling pathways, including the PI3K-AKT signalling pathway, cytokine receptor-cytokine interaction, JAK-STAT signalling pathway, MAPK signalling pathway, and cancer pathways [27].…”
Section: біотехнології та біоінженеріяmentioning
confidence: 99%